Development of scientific and methodological approaches to improve the efficiency of quarry transport operation - A. N. Novikov; I. A. Novikov; N. A. Zagorodnij; A. S. Semykina (Вестник СибАДИ)
Introduction. The article discusses innovative and information technologies, an identification system, the purpose of which is to increase the efficiency of the operation of open pit transport. An algorithm for the operation of vehicles in a quarry in a simulation model has been developed. The method of calculating the rational amount of quarry transport for the transportation of iron ore from the place of extraction in the quarry to a temporary storage point is presented.Methods and materials. To manage the transportation process at GOK, it is required to use improved methods and methods for optimizing transport flows to reduce costs in the system “quarry-warehouse / processing plantproduction”, taking into account the dynamics of processes. To increase the efficiency of the operation of open-pit vehicles, the use of innovative and information technologies, an identification system is required. As a scientific and methodological approach, preliminary registration of open pit transport and fixing the time of loading and unloading processes, cargo movement are used. To organize the operation of the transportation process, it is necessary to develop an algorithm for the operation of open pit transport in a simulation model, which will allow collecting information about the state of all temporary storage points, the duration of the transportation process, etc. The implementation of the results of using the methodology for calculating a rational number of vehicles allows to achieve an effective raw materials from the quarry to a temporary storage point.Results. The authors have developed scientific and methodological approaches to improve the efficiency of mining transport operation.Conclusion. Research of the organization of work of the process of transportation of iron ore raw materials at the mining and processing plant has been carried out. It is concluded that it is necessary to develop scientific and methodological approaches to improve the operation of open pit transport. An algorithm for the operation of open pit transport in a simulation model has been developed, which allows taking into account the influence of the control and distribution system of dump trucks on the number of excavators and the timely delivery of dump trucks to storage points. The method of calculating the rational amount of quarry transport for the transportation of iron ore raw materials is presented.